2021
DOI: 10.1111/evj.13409
|View full text |Cite
|
Sign up to set email alerts
|

Non‐banked curved tracks influence movement symmetry in two‐year‐old Standardbred trotters

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…These thresholds have been adjusted to the method of data construction used in other IMU systems [ 15 ]. A growing number of studies have used these thresholds as an objective lameness detection [ 11 , 12 , 16 ]. However numerous asymmetry values of sound horses have been over these thresholds [ 8 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These thresholds have been adjusted to the method of data construction used in other IMU systems [ 15 ]. A growing number of studies have used these thresholds as an objective lameness detection [ 11 , 12 , 16 ]. However numerous asymmetry values of sound horses have been over these thresholds [ 8 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The loading on the outside and inside limbs can be affected by both the degree of camber on a bend and the gait at which the horse negotiates the banked curvature, as this affects the duty factor, so both the degree of track camber and speed of the horse negotiating the bend need to be considered when assessing the mechanical loading of the inside and outside limbs during exercise on an elliptical track [5,41,42]. Training surfaces in both Hong Kong and Singapore are banked at their corners so consideration of the potential affect that banking and camber may have on the symmetry of movement of the horses sampled in this study should be given.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature it is reported that the curve in a circuit is a significative factor in the pathogenesis of racehorses' injuries [3,24,25]. Kinematics of movement on a curved track has been recently investigated in horses at trot [26] and at gallop [27] on racetracks where the radius of the curve ranged from 85 to 200 m. In horses galloping on a curve at around 14 m/s, the entire limb and the third metacarpal bone inclination increase, to counterbalance the elevated centripetal acceleration acting perpendicular to the direction of motion [3,27]. At the extremal point of a curve, a horse generally experiences forces that are smaller than what would be predicted by mathematical models [28].…”
Section: Discussionmentioning
confidence: 99%